HUBUNGAN ANTARA IKLIM ORGANISASI DENGAN PERILAKU KEWARGAAN ORGANISASI PADA KARYAWAN DI PERUSAHAAN RITEL - Putu Aninditha Veera Laksmi; Nicholas Simarmata (Jurnal Psikologi Udayana, 2015)
The improvement of house needs which is added by modern life style, it creates the modern shop pattern in society when fulfilling their needs. Retail Company tries to fulfill society needs by selling products and service that is done by its employees. Therefore, the employees have an important role and they are hoped to emerge extra behavior for the company effectiveness. The company needs employees who do an extra behavior more than their formal job description and they perform to support with company’s hope (Robbins, 2001). In another words, employee does Organizational Citizenship Behavior (OCB). When employees work, they will always connect with their work environment. OCB on employees will be high if they present in a positive organization climate. This research aims to know the relationship between organization climate and organization citizenship behavior in Retail Company employee. Respondents of this research are 95 employees working in 4 Retail Companies. The sampling method is cluster random sampling. The data collecting method is organization climate scale and organization citizenship behavior scale. This research uses content validity and Alpha Cronbach reliability. The reliability of organization climate scale is 0,937 and organization citizenship behavior scale is 0,965. The data distribution of organization climate and organization citizenship behavior is normal (z=0,327; z=0,058; p>0,05). The relationship between organization climate and organization citizenship behavior variable is linear (F=0,000; p<0,01). This research is a quantitative research which its data analysis is simple regression. The result of this research shows that the coefficient regression is 0.720 and the coefficient correlation is 0.568 with its significance 0,000 (p<0.01). This result proves that there is a positive relationship between organization climate and organization citizenship behavior in retail company employee. The contribution of organization climate variable toward organization citizenship behavior variable is 32.2%. Keywords: organization climate, organizational citizenship behavior, employee, retail company